Effects of Unilateral Prefrontal Lesions on Familiarity, Recollection, and Source Memory - Duarte, Audrey (J Neurosci, 2005)
Recognition memory can be supported by both the assessment of the familiarity of an item and by recollection of the context in which an item was encountered. Some have hypothesized that the prefrontal cortex (PFC) disproportionately contributes to recollection, whereas an alternative view is that the PFC contributes to both recollection and familiarity. Here, we examined the effects of prefrontal lesions on recollection and familiarity. Patients with unilateral PFC lesions and age-, gender-, and education-matched controls encoded pictures of meaningful objects that were presented briefly to the left or right visual field and subsequently performed recognition tests for centrally presented objects. Laterality effects within the PFC were also assessed in relation to recollection and familiarity processes. Patients with prefrontal lesions showed impaired familiarity-based recognition, and this deficit was specific for objects encoded by the lesioned hemisphere. In addition, recollection of the context in which each item was encountered was impaired independent of the visual field of presentation in patients with left prefrontal lesions. Recollection measured by subjective reports (“remember”) was not impaired in either left or right frontal patients. These findings suggest that the PFC plays a critical role in recognition memory based on familiarity as well as recollection. Furthermore, these results suggest that left PFC regions are critical for source recollection.